A Decade of Youth Behavior Studies Regarding ICT's Impacts: Notes on the Experience of School of the Future Research Laboratory at the University of São Paulo - Brazil - Brasilina Passarelli; Alan César Belo Angeluci (Journal of Systemics, Cybernetics and Informatics)

(untitled)
School of the Future Research Laboratory at the University of São Paulo – USP is 32 years old and since 2010 has been devoted to map and discuss new behaviors among different virtual communities seeking of media and information literacy (MIL), new ways of learning and producing contents on digital platforms. On order to do so we have been developing surveys, virtual ethnography and netnographic studies to map new attitudes and behaviors of contemporary networked actors. This article brings a summary of several findings in the research conducted in the last ten years, demonstrating how the pioneering work of School of the Future researchers points out indicators on the behavior of young communities that are valid to this day and still raise contemporary discussions. In order to do so we will focus on our most extensive netnographic studies developed with young students throughout Brazil in 2012-2014.